An overview of low resolution quantization in wireless communication system - Dan QIAO; Chaokai WEN; Feifei GAO; Shi JIN (Dianxin kexue)
Compared to the 4th generation (4G) mobile communication technology,the 5th generation (5G) mobile communication technology will provide tens of times of peak rate increase,reaching up to several thousands megabit per second.The coming wireless communication systems face the problems of expensive hardware cost and high power consumption,which is becoming a bottleneck of high-rate communication systems.To cope with these problems,redesigning communication systems with the receiver using finite precision analog-to-digital converters (ADC) is one possible approach.The analysis of recent information theory for the AWGN channel shows that the performance loss due to 2~3 bit ADC acceptable.The application of low resolution quantization in wireless communication systems was focused on,an overview of the channel capacity and receiver design under low-precision ADC was provided.